An Empirical Analysis of the Determinants of Skill Gap: A Case Study of the Rural Food Processing Industry of the Bihar State of India - Kumari, Anupma; Gupta, Amisha (AMC Indian Journal of Entrepreneurship, 2024)
Purpose : When an organization lacks the abilities needed to complete a critical task, it can impede its growth and ability to compete. This is known as a skill gap. This leads to a drop in output as well as subpar performance and quality. The â€œMake in Indiaâ€ and â€œSkill Indiaâ€ initiatives, which were introduced in 2014 and 2015, respectively, have brought the skill gap considerable attention as a growing area of concern. Our main goal in this research is to look into and examine the variables that lead to skill gaps in Indian workers in the food processing sector. Methodology : The study is based on the primary data, which were collected by a field survey method. We selected seven factors based on the literature review and analyzed the impacts of these factors on the skill gap possessed by the workers in the food processing industry. For the analysis, we used a multiple regression model, which is found to be a good fit for predicting the impact of the independent variables on the dependent variable (Adjusted R2 value = 0.88; F value = 219.40; p = 0.00). In this regression model, the variables that generate the skill gap are considered independent variables, while the skill gap itself is considered a dependent variable. Findings : The highest and statistically significant impact on the skill gap (Î²5 = 0.254) is found in the regression model analysis for the factor â€œLow investment in skill development training program,â€ while the factor â€œNon-awareness of skill development training programâ€ has a relatively low impact (Î²7 = 0.123). Practical Implications : The study would enable food processing industry plant managers and legislators to create efficient plans to train a qualified workforce, close the skills gap in the sector, and contribute to the nation's demographic dividend. Originality : The literature study shows that qualitative analysis has been used in the majority of skill gap analysis studies in the Indian food processing industry. There has never before been an empirical investigation of the talent gap by a researcher. Thus, this work would contribute fresh information and literature for more research in this field.